2000
DOI: 10.1021/jm990492u
|View full text |Cite
|
Sign up to set email alerts
|

Gold(III) Complexes as Potential Antitumor Agents: Solution Chemistry and Cytotoxic Properties of Some Selected Gold(III) Compounds

Abstract: Gold(III) complexes generally exhibit interesting cytotoxic and antitumor properties, but until now, their development has been heavily hampered by their poor stability under physiological conditions. To enhance the stability of the gold(III) center, we prepared a number of gold(III) complexes with multidentate ligands - namely [Au(en)(2)]Cl(3), [Au(dien)Cl]Cl(2), [Au(cyclam)](ClO(4))(2)Cl, [Au(terpy)Cl]Cl(2), and [Au(phen)Cl(2)]Cl - and analyzed their behavior in solution. The solution properties of these com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
221
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(237 citation statements)
references
References 23 publications
12
221
0
Order By: Relevance
“…This indicated that a bidentate ethylenediamine ligand stabilized the Au(III) oxidation state against reduction, as previously reported for chelating N donor ligands. 31 The position of the peaks B, B1, and C, which developed on consecutive voltammetric scans, was essentially not influenced by the composition of the gold complex. The gold complexes displayed good electrochemical stability as indicated by their peak currents and peak potentials, which were stable (± 10%) at least for 4 h.…”
Section: Electrochemistry Of Gold Complexesmentioning
confidence: 93%
“…This indicated that a bidentate ethylenediamine ligand stabilized the Au(III) oxidation state against reduction, as previously reported for chelating N donor ligands. 31 The position of the peaks B, B1, and C, which developed on consecutive voltammetric scans, was essentially not influenced by the composition of the gold complex. The gold complexes displayed good electrochemical stability as indicated by their peak currents and peak potentials, which were stable (± 10%) at least for 4 h.…”
Section: Electrochemistry Of Gold Complexesmentioning
confidence: 93%
“…Gold compounds (Table 1) were selected based on known ability of AF and GSTM to inhibit TrxR (Fricker et al, 1996;Simon et al, 2000;Gromer et al, 2004) or proposed use as therapeutic agents for arthritis or cancer (Messori et al, 2000;Che et al, 2003;Messori et al, 2004). Stock solutions of the gold compounds were added to the enzyme mixture to provide an appropriate final concentration range before the enzyme mixture was added to the substrate-buffer mixture.…”
Section: Gold Compound Inhibitorsmentioning
confidence: 99%
“…Some gold(I) complexes, such as auranofin and aurothiomalate, have been used very successfully in the treatment of rheumatoid arthritis [2], while gold(III) complexes have gained considerable attention as potential antitumor agents [3]. During the recent years, a large number of gold(III) complexes, in which the reduction potential of the Au(III) was lowered by the use of polydentate ligands, have been reported to be appreciably stable under physiologically relevant conditions and to manifest relevant cytotoxic activity against different human tumor cell lines [4][5][6][7][8][9][10][11][12][13][14][15][16]. The possible involvement of gold(III) complexes in cancer treatment initiated an interest in the area of gold(III) interactions with different biologically important ligands, such as amino acids and peptides [17].…”
Section: Introductionmentioning
confidence: 99%